2021
DOI: 10.1002/cbic.202000854
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxy Radical Reactivity of Nucleic Acids: Practical Implications for Biotinylation

Abstract: Recent advances in peroxidase-mediated biotin tyramide (BT) signal amplification technology have resulted in high-resolution and subcellular compartment-specific mapping of protein and RNA localization. Horseradish peroxidase (HRP) in the presence of H 2 O 2 is known to activate phenolic compounds for phenoxy radical reaction with nucleic acids, where biotinylation by BT is a practical example. BT reactivity with RNA and DNA is not understood in detail. We report that BT phenoxy radicals react in a sequence-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…We have previously shown that peroxidase-based biotinylation of oligodeoxyribonucleotides with BT is enabled by DNA conjugation with 5’ fluorescein and we described structural details of BT-fluorescein adducts [6]. We demonstrated that an in vitro streptavidin gel shift assay is capable of detecting biotinylation of both RNA and 5’-fluorescein-modified DNA oligonucleotides and, importantly, provided molecular insights into differences in RNA and DNA biotinylation.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously shown that peroxidase-based biotinylation of oligodeoxyribonucleotides with BT is enabled by DNA conjugation with 5’ fluorescein and we described structural details of BT-fluorescein adducts [6]. We demonstrated that an in vitro streptavidin gel shift assay is capable of detecting biotinylation of both RNA and 5’-fluorescein-modified DNA oligonucleotides and, importantly, provided molecular insights into differences in RNA and DNA biotinylation.…”
mentioning
confidence: 95%
“…To determine if other biological functional groups are reactive with BT phenoxy radicals, we devised a competition assay for the assessment of all other natural amino acids. In this assay, a streptavidin gel shift is used to detect horseradish peroxidase (HRP)and H 2 O 2 -dependent radical biotinylation of 5’-fluorescein modified oligodeoxyribonucleotide LJM-6132 [6]. Increasing concentrations of individual competing amino acids are added to the reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BioID and TurboID Biotin ligases catalyze synthesis of a highly reactive biotinyl-5′-adenylate intermediate from biotin and ATP, allowing proximity biotinylation of primary amine nucleophiles as reactive targets. ,, While such targets exist in proteins on lysine residues and N-termini, none are found in nucleic acids. APEX and APEX2, on the other hand, catalyze production of short-lived reactive phenoxy radical intermediates from biotin tyramide (BT) in the presence of H 2 O 2 . , Though proximity biotinylation by peroxidases has the impressive advantage of dual protein and RNA radical biotinylation, this approach cannot be used directly for biotinylation of unmodified DNA …”
mentioning
confidence: 99%
“…It is known that tyrosine residues are protein reactive sites biotinylated by APEX2-generated BT phenoxy radicals. , To determine if other biological functional groups are reactive with BT phenoxy radicals, we devised a competition assay for the assessment of all other natural amino acids. In this assay, a streptavidin gel shift is used to detect horseradish peroxidase (HRP) and H 2 O 2 -dependent radical biotinylation of 5′-fluorescein-modified oligodeoxyribonucleotide 6132 . Increasing concentrations of individual competing amino acids are added to the reaction.…”
mentioning
confidence: 99%